Development and Evaluation of Instructional Module for Special Program in Journalism - Jayson O. Yongco; Jasper M. Del Valle (International Journal of Educational Management and Development Studies, 2022)
The study aimed to develop and evaluate the instructional module for special program in journalism for grade 8 students. It is geared towards probing the errors encountered in learning resource construction and the recommendations in enhancing the instructional material through questionnaires and guidelines for learning resource material (LRM) production. Data were gathered from forty Grade 8 Journalism students enrolled at an Integrated High School in Laguna, Philippines and ten specialists who were purposively selected. The data were collected and treated using Mean. Findings revealed that the student-evaluators strongly agree on the rating criteria of the instructional module in terms of format, content, clarity and usefulness. On the other hand, the specialists rated the instructional module passed on content, format and presentation and organization criteria but failed on accuracy and up-to-datedness of information.